Heart Rate Variability as a Possible Biomarker of Cognitive-Motor Integration in Post-Stroke Patients. - Penati, Rachele; Robustelli, Alessandro; Gasperini, Giulio; Specchia, Alessandro; Paleari, Valeria; Guanziroli, Eleonora; Molteni, Franco (Advances in Rehabilitation Science & Practice, 2025)
Heart Rate Variability (HRV) refers to variation in time intervals between consecutive heartbeats, indicating autonomic nervous system's control over the heart. Time and frequency analysis of HRV could serve as predictors for severity and functional outcome in stroke. Aim of this study is to verify if HRV, measured during cognitive and sensorimotor upper limb (UL) tasks, can be used as a biomarker of cognitive-motor interaction in post-stroke patients. Forty-six patients with unilateral brain injury following stroke were enrolled: 27 (58.7%) ischemic, 19 hemorrhagic, 24 (52.2%) subacute (<6 months), and 22 chronic. Mean age at evaluation was 61 years. Right side was affected in 16 subjects (34.8%). Each patient underwent HRV recording in the following conditions: (1) Rest (5 minutes); (2) Visuomotor simulation training of the affected upper limb (UL) using Dessintey IVS3 (DE, 5 minutes); (3) Motor Imagery of the affected UL (MI, 5 minutes). UL functional outcome measures were collected for both affected and less affected sides. All patients showed reduced HRV in time and frequency domains and sympathetic tone predominance at rest. During DE and MI, a significant reduction in time domain was observed. In frequency domains, low frequency decreases during DE, with parasympathetic tone predominance. In the subgroup analyses for lesion side, only right hemiparetic patients showed parasympathetic predominance during mental tasks of the upper limb (DE and MI. No correlation was found between HRV parameters and UL functional scales. Different HRV response in time and frequency domains to mental task was observed between right and left hemiparetic subjects. This could be explained by different anatomical-functional substrates between right and left hemisphere and could reflect different behaviors during UL cognitive-motor tasks. HRV parameters were not correlated with clinical functional assessment scales, likely meaning that they possible exploring different domains.